Metamorphosis: A qualitative study exploring menopause through body-based practices - Sara Smyth; Tina Cartwright (Journal of Health Psychology, 2026)
Menopause is a multidimensional life transition, yet UK healthcare and public discourse often frame it narrowly around hormones and medical treatment. This qualitative study explored how 18 women aged 40–60 used body-based practices, including strength training, yoga and cold-water immersion, to navigate menopause. Interviews were analysed using reflexive thematic analysis within a critical realist framework. Menopause was interpreted as an individual biopsychosocial-cultural experience, with spiritual and experiential dimensions for some. Psychological symptoms were typically more disruptive than physical ones, and limited professional support prompted women to create personalised “toolkits,” often blending hormone therapy with body-based practices. Participants described practices as supporting symptom relief, self-awareness and identity development, with enjoyment and self-efficacy influencing continued engagement. Participants became informal educators and advocates for earlier education and inclusive, evidence-based resources. However, the sample was relatively privileged and health-literate. Findings support whole-person menopause care that promotes agency while recognising unequal access to resources.